Relationship between pain intensity, disability, exercise time and computer usage time and depression in office workers with non-specific chronic low back pain - Hong, SoungKyun; Shin, DooChul (Medical hypotheses, 2020)
The purpose of this study was to investigate the relationship between pain intensity, disability, exercise time, and computer use time and depression in office workers with nonspecific chronic low back pain. A cross-sectional correlational study. Sixty-one office workers diagnosed with nonspecific chronic low back pain The participants' body mass index was calculated using their height and weight. The amount of time the participants spent using a computer or exercising per week was analysed. The Beck Depression Inventory was used to determine the degree of depression in the participants. The Oswestry disability index and the numeric pain rating scale were used to assess the severity and pain intensity of the participants. There was a significant correlation between the Beck Depression Inventory, the Oswestry disability index (r = 0.419, p < .05), and the computer use time (r = 0.369, p < .05) of the participants. There was a correlation between the Oswestry disability index and the numeric pain rating scale (r = 0.677, p < .01). There were significant correlations among the sub items of the Oswestry disability index with the Beck Depression Inventory, in the order of personal management activities (r = 0.539, p < .01), standing (r = 0.519, p < .01), social activities (r = 0.421, p < .05), travelling (r = 0.381, P < .05), and walking (r = 0.357, p < .05). Our hypothesis as a results of this study is that the depression of office workers with non-specific chronic low back pain is correlated with the computer using time and the degree of disability. Especially among their various disabled items, personal management activities, standing, social activities, travelling, and walking is related to depression.